Solar irradiation of the seed germination stimulant karrikinolide produces two novel head-to-head cage dimers - Scaffidi, A.; Waters, M.; Skelton, B.; Bond, C.; Sobolev, A.; Bythell-Douglas, R.; McKinley, A.; Dixon, Kingsley; Ghisalberti, E.; Smith, S.; Flematti, G. (2012)
Karrikinolide is a naturally derived potent seed germination stimulant that is responsible for triggering the germination of numerous plant species from various habitats around the world. We now report that solar irradiation of karrikinolide yields two novel head-to-head cage photodimers with the formation, stability and bioactivity of both presented herein.